2021
DOI: 10.1177/09603271211003634
|View full text |Cite
|
Sign up to set email alerts
|

The effect of baicalein on endoplasmic reticulum stress and autophagy on liver damage

Abstract: Carbon tetrachloride (CCl4) is a toxic chemical that causes liver injury. CCl4 triggers endoplasmic reticulum (ER) stress and unfolded protein response (UPR). UPR triggers autophagy to deal with the damage. The aim of this study was to investigate the effect of baicalein, derived from Scutellaria baicalensis, on CCl4-induced liver damage concerning ER stress and autophagy. Two groups of Wistar albino rats (n = 7/groups) were treated with 0.2 ml/kg CCl4 for 10 days with and without baicalein. Histological and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…It has also been published that ER stress invokes liver fibrosis primarily due to ER stress within HSCs due to their activation ( Koo et al, 2016 ). Since hepatocytes are known to be sensitive to CCl 4 -mediated ER stress ( Üstüner et al, 2021 ), we examined whether crosstalk between activated HSCs and hepatocytes in a co-culture system promoted the ER stress response in hepatocytes and whether AKAP12 regulated this crosstalk. Modulating HSC activation through AKAP12 regulated the ER stress response in hepatocytes in culture.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been published that ER stress invokes liver fibrosis primarily due to ER stress within HSCs due to their activation ( Koo et al, 2016 ). Since hepatocytes are known to be sensitive to CCl 4 -mediated ER stress ( Üstüner et al, 2021 ), we examined whether crosstalk between activated HSCs and hepatocytes in a co-culture system promoted the ER stress response in hepatocytes and whether AKAP12 regulated this crosstalk. Modulating HSC activation through AKAP12 regulated the ER stress response in hepatocytes in culture.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have suggested that baicalein may regulate autophagy in liver cancer cells to promote apoptosis and enhance chemosensitivity [ 44 , 47 ]. In addition, baicalein has also been shown to protect liver cells from damage through autophagy [ 38 , 48 ]. However, how baicalein regulates hepatic autophagy is still unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have noted that baicalein represses the phosphorylation of mTOR and activates ULK1 signaling [ 79 , 80 ], suggesting that baicalein may activate hepatic autophagy by suppressing the activation of mTOR and/or ULK phosphorylation. Moreover, a recent study showed that baicalein triggered ER stress to protect the liver from CCl 4 -induced damage [ 48 ]. In accordance with these findings, whether ER stress and downstream unfolded protein response (UPR) signaling can trigger the initiation of baicalein-induced autophagy by transcriptionally controlling ATG gene expression in liver cells can be examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been published that ER stress invokes liver fibrosis primarily due to ER stress within HSCs due to their activation (36). Since hepatocytes are known to be sensitive to CCl4-mediated ER stress (52), we examined whether crosstalk between activated HSCs and hepatocytes in a co-culture system promoted the ER stress response in hepatocytes and whether AKAP12 regulated this crosstalk. Modulating HSC activation through AKAP12 regulated the ER stress response in hepatocytes in culture.…”
Section: Discussionmentioning
confidence: 99%